2014
DOI: 10.4049/jimmunol.1301158
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Metabolically Licenses T Cells for Activation To Link Nutrition and Immunity

Abstract: Immune responses are highly energy dependent processes. Activated T cells increase glucose uptake and aerobic glycolysis to survive and function. Malnutrition and starvation limit nutrients and are associated with immune deficiency and increased susceptibility to infection. While it is clear that immunity is suppressed in times of nutrient stress, mechanisms that link systemic nutrition to T cell function are poorly understood. We show here that fasting leads to persistent defects in T cell activation and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
241
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(257 citation statements)
references
References 69 publications
13
241
1
2
Order By: Relevance
“…2013a, 2013b; Iles et al, 2013), it is unlikely to offset nutritional deficiency resulting from lost foraging opportunities on lipid-rich marine mammal prey (Rode et al, 2015). Perhaps simultaneously, increased resource allocation to facilitate extended swimming or foraging bouts due to diminishing sea ice could affect immune function or efficiency (Saucillo et al, 2014). Moreover, nutritional deficiency could mobilize contaminants stored in blubber, further taxing immune function (Letcher et al, 2010) and facilitating disease susceptibility.…”
Section: Resultsmentioning
confidence: 98%
“…2013a, 2013b; Iles et al, 2013), it is unlikely to offset nutritional deficiency resulting from lost foraging opportunities on lipid-rich marine mammal prey (Rode et al, 2015). Perhaps simultaneously, increased resource allocation to facilitate extended swimming or foraging bouts due to diminishing sea ice could affect immune function or efficiency (Saucillo et al, 2014). Moreover, nutritional deficiency could mobilize contaminants stored in blubber, further taxing immune function (Letcher et al, 2010) and facilitating disease susceptibility.…”
Section: Resultsmentioning
confidence: 98%
“…Leptin is a hormone whose primary role is to regulate glucose uptake and fat deposition, and reduced levels thereof have been reported in malnourished individuals (22). Recent data suggest that leptin, in addition to its metabolic functions, is essential for activation of effector T cells (21), and leptin has even been suggested as a potential vaccine adjuvant (49). It would be highly relevant in future TB PEM studies to monitor leptin levels and the potential role of leptin supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cellular part of the immune system has, in early studies, been reported to be sensitive to the effects of PEM (15,16), resulting in reduced production of the T helper type 1 (Th1) cytokines gamma interferon (IFN-␥) and interleukin-2 (IL-2) (17)(18)(19)(20). The cellular and molecular background of this reduced response is not fully understood and has been the subject of some debate (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…However, confounding immune effects of streptozotocin (12,13) and disrupted leptin signaling (14) complicate interpretation of these studies. Similarly, since autoimmunity can influence alloimmunity (15), the NOD model is also not suitable to address how chronic hyperglycemia itself affects alloimmunity.…”
Section: Introductionmentioning
confidence: 99%